PENGGUNAAN METODE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR BUDAYA ALAM MINANGKABAU (BAM) PADA SISWA KELAS VIII 4 SMPN 14 PADANG - MELDRIANTI, Drs. Abd Hafiz, M.Pd, Drs. Ajusril S (Universitas Negeri Padang, 2013)
One of the methods that can improve student learning outcomes in subjects BAM is talking stick method, using the media stick. The study was conducted using action research, the research subjects were students of class VIII 4 SMP 14 Padang. Researchers collaborate with colleagues to carry out research in two cycles in collecting student data. Then the data is processed by using the t test an increase in the percentage of student learning outcomes, with satisfactory results, it is seen from the average pre cycle of 68.5 to an average of 76.16 in the first cycle and an average of 86.16 on the implementation of the second cycle. This means an increase in the average learning outcomes of pre-cycle to the first cycle of 7.66 and from cycle I to cycle II of 10.00. From pre-cycle to cycle I 3,357 t> t table 1.031 and from cycle I to cycle II 5.282 t count> t table 1.031. Thus the hypothesis proposed action proved correct. Application of the method are done talking stick is a good teacher in the learning process proved to be effective in improving student learning outcomes. Keywords: Methods talking stick, BAM, Improved Learning Outcomes.